Can Interaction of Performance Measurement, Remuneration, and Financial Management System Improve Performance of Indonesian State Universities? - Fajar Gustiawaty Dewi; Rindu Rika Gamayuni; Agrianti Komalasari (Goodwood, 2026)
Purpose: This study aims to examine whether the interaction between performance measurement, remuneration, and financial management systems can improve the performance of Indonesian state universities within the context of governance reforms and increased institutional autonomy. Methodology: Data were obtained from secondary sources, including archival and observational data of state universities in Indonesia, with financial management statuses of legal entities, public service agencies, and government work units. The sample was selected using purposive sampling, focusing on state universities that published annual reports between 2017-2023 period. Before the Moderated Regression Analysis (MRA) testing, classical assumption tests were conducted to ensure the validity of the model. Results: The findings indicate that performance measurement, remuneration systems, and financial management systems significantly affect state university performance. Conclusions: This study provides empirical evidence that can be utilized for policymaking to enhance the performance of state universities. State universities must strengthen performance measurement systems that include key and additional performance indicators to ensure more comprehensive performance evaluations. Limitations: This study has limitations because several variables were difficult to measure and required the use of categorical measurements. Contributions: This study contributes to the public sector accountability and organizational change literature by proposing a multidimensional framework that integrates performance measurement, remuneration, and financial governance.